SOSIALISASI KOORDINASI MATA DAN KAKI PADA PASSING DAN STOPPING SSB UIR PEKANBARU - Toktong Parulian; Purba Andi Wijaya; Rohima Rohima (Bajang Institute, 2023)
Football is a high intensity sport with a playing time of 2x45 minutes. For this reason, the game of football requires extraordinary basic skills. One of the main skills in this game is passing and stopping. Problems on the field are that many athletes make mistakes so that the ball doesn't flow smoothly. Many players make passing and stopping errors. This is thought to be due to a lack of passing and stopping practice. The solutions offered by the researchers are: 1) explain in theory the extent of the importance of passing and stopping in football and the various forms of passing training, 2) create a training program to improve passing, 3) implement an example of a program to improve passing and stopping training in football games . The results of this service: From the socialization that has been carried out, everything has gone well and smoothly, although there are a few obstacles where not all SSB UIR participants or children are present at the socialization so that children who are not present at the socialization do not receive knowledge or input from the service team for improvement. and stop it